Brown bear, brown bear, what do you see? - Martin, Bill, 1916-2004.; Carle, Eric (New York : H. Holt, 1992)
Children see a variety of animals, each one a different color, and a teacher looking at them.
Originally published: New York : Holt, Rinehart, and Winston, 1967.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
1.4.
1.4
Keywords: Animals -- Fiction; Color -- Fiction; Stories in rhyme; Animals -- Fiction; Color -- Fiction; Stories in rhyme